A study on the impact of short structured laparoscopy training course: Fellowship of Indian Association of Gastrointestinal Endo Surgeons - Sundaram Easwaramoorthy; Sakthivel Chandrasekar; Kanagavel Manickavasakam; Pranesh Sridhar; Gurusamy Govindan; Haridra Sundarrajan (Journal of Minimal Access Surgery)
Introduction: Since the invention of laparoscopic cholecystectomy, there have been tremendous developments in minimal access surgery and an increasing need for well-structured laparoscopic training courses. There is a need to analyse the real benefit of short training courses. The study was conducted to find whether a focused 3-day structured laparoscopy training course conducted by the Indian Association of Gastrointestinal Endo Surgeons (IAGES) could improve the cognitive and technical skills of surgeons in essential laparoscopic surgery. Materials and Methods: The Indian Association of Gastrointestinal Endo Surgeons conducted this prospective study during 2023–2024. Five hundred and fifty one candidates under the examination category in 14 consecutive courses were considered as the study groups to compare their pre- and post-test multiple-choice question (MCQ) scores to find the improvement in their knowledge base. A survey of candidates using Google Forms was also done at 6 months to find out the impact of the course. The following outcome measures were analysed: